2006
DOI: 10.1002/bit.21263
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of GS‐NS0 cells producing a recombinant monoclonal antibody during fed‐batch culture

Abstract: In this study we have analyzed the dynamic covariation of the mammalian cell proteome with respect to functional phenotype during fed-batch culture of NS0 murine myeloma cells producing a recombinant IgG(4) monoclonal antibody. GS-NS0 cells were cultured in duplicate 10 L bioreactors (36.5 degrees C, 15% DOT, pH 7.0) for 335 h and supplemented with a continuous feed stream after 120 h. Cell-specific growth rate declined continuously after 72 h of culture. Cell-specific recombinant monoclonal antibody productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 42 publications
5
27
0
Order By: Relevance
“…It increases until day 4 and decreases subsequently. A similar profile for productivity has been reported earlier in a study with GS-NSO cells (Stansfield et al 2007), where productivity of MaB increased up to day 8, and declined thereafter in a fed-batch culture. Other studies have also shown a similar productivity profile (Kaufmann et al 1999;Hendrick et al 2001;Yoon et al 2006a, b).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It increases until day 4 and decreases subsequently. A similar profile for productivity has been reported earlier in a study with GS-NSO cells (Stansfield et al 2007), where productivity of MaB increased up to day 8, and declined thereafter in a fed-batch culture. Other studies have also shown a similar productivity profile (Kaufmann et al 1999;Hendrick et al 2001;Yoon et al 2006a, b).…”
Section: Discussionsupporting
confidence: 85%
“…Note that this promoter has been reported to possess sites for many different transcription factors (Sambucetti et al 1989;Yurochko et al 1997). It is interesting to note that IgG HC and LC were also under the control of the same promoter in the GS-NSO cells used in the study mentioned above (Stansfield et al 2007). The expression from this promoter seems to be inversely related to growth.…”
Section: Discussionmentioning
confidence: 99%
“…Productivity data suggested that the overall reduction in cell concentration is the main limiting factor in photo‐damaged medium, as was reported elsewhere 28. However, it was found that additionally the IgG processing machinery seems to be altered in light‐irradiated medium, and the ‘intracellular titer’ is somewhat decoupled from the extracellular concentration.…”
Section: Discussionsupporting
confidence: 73%
“…Hence, it is very difficult to distinguish between cellular changes resulting from the decrease in growth rate and increase in q. A substantial effect of changes in growth rate on the proteome of GS-NS0 cells during fed-batch cultures was confirmed by Stansfield and coworkers [19]. They observed that both q and growth rate varied during culture, each following a distinct pattern.…”
Section: Experimental Limitationsmentioning
confidence: 86%
“…Changes in growth rate have a significant impact on the proteome [19], possibly explaining why structural and growth-related proteins accounted for the largest differences between the cell lines [18].…”
Section: Improving Metabolismmentioning
confidence: 99%